2016
DOI: 10.1038/srep25022
|View full text |Cite
|
Sign up to set email alerts
|

A Laminated Microfluidic Device for Comprehensive Preclinical Testing in the Drug ADME Process

Abstract: New techniques are urgently needed to replace conventional long and costly pre-clinical testing in the new drug administration process. In this study, a laminated microfluidic device was fabricated to mimic the drug ADME response test in vivo. This proposed device was loaded and cultured with functional cells for drug response investigation and organ tissues that are involved in ADME testing. The drug was introduced from the top of the device and first absorbed by the Caco-2 cell layer, and then metabolized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…Viability of liver cancer cells HepG2, breast ones MDA MB 231, and vascular endothelial cells EAhy926 was evaluated aer they were cultivated on the microsystem for 72 h. PDMS has been demonstrated to be a biocompatible material with a vast array of cell types. 21 Consistent with previous studies, 22 our results also conrmed that cancer and endothelial cells showed around 97% viability on the microdevice aer 3 days of cultivation ( Fig. 2A and B), indicating that the laminated PDMS microuidic devices almost had no detrimental effects on cell survival.…”
Section: Microfabrication and Evaluation Of The Microuidic Devicesupporting
confidence: 92%
See 1 more Smart Citation
“…Viability of liver cancer cells HepG2, breast ones MDA MB 231, and vascular endothelial cells EAhy926 was evaluated aer they were cultivated on the microsystem for 72 h. PDMS has been demonstrated to be a biocompatible material with a vast array of cell types. 21 Consistent with previous studies, 22 our results also conrmed that cancer and endothelial cells showed around 97% viability on the microdevice aer 3 days of cultivation ( Fig. 2A and B), indicating that the laminated PDMS microuidic devices almost had no detrimental effects on cell survival.…”
Section: Microfabrication and Evaluation Of The Microuidic Devicesupporting
confidence: 92%
“…During the proliferative phase of tumor cells, functional vasculature and interstitial uid ow may have major inuence on drug transport. 22 At the stage of tumor cell intravasation, due to the barrier function of vascular endothelial cells 28 and the different invasion style of various tumor cells, 41 the inhibitory effects of drugs on tumor cells intravasation may be different. Therefore, tumor-vascular models such as our dynamic micro-uidic platform may become capable of recapitulating the desired, human-mimicking, and nuanced responses to drug treatment at different phases of tumor metastasis.…”
Section: Intravasation and Adherence Of Different Tumor Cells Onto Enmentioning
confidence: 99%
“…82,83 An alternate approach, which is currently pursued, is represented by so-called "organ-on-a-chip" models. [97][98][99] Such approaches might be combined or paralleled by in silico approaches. 100,101 Although physiologically based pharmacokinetic modeling approaches involve transport and metabolism 102,103 and are combined with wet lab approaches (e.g., drug sulfonation 104 ), it might be interesting to further evolve such models by taking into account a possible specific special arrangement of transporters and drug-metabolizing enzymes in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The type of cells (single or multiple origins), the direct microenvironment of cells, the medium preserving differentiated states of different cells, as well as the three-dimensional (3D) configuration of tissues may all impact outcome measures. Further features to consider include dose–response characterizations and the developmental stages of selected cells [ 21 , 22 ].…”
Section: Drug Testing and Design Of Bocmentioning
confidence: 99%